Answers:
-6x+4+3x-2= -6x+3x+4-2= -3x+2
7(x + 2) + 3 = 73
Multiply the bracket by 7
7x+14+3= 73
7x+17= 73
7x= 73-17
7x=56
Divide by 7
7x/7= 56/7
x= 8
3-7x+4x-10= -7-3x
4k-14+3k=21
7k-14= 21
Move -14 to the other side. Sign changes from -14 to +14.
7k-14+14= 21+14
7k= 35
divide by 7
7k/7= 35/7
k= 5
5(-4x+2)+9x
Multiply the bracket by 5
-20x+10+9x= -11x+10
h-6+7h=42
8h-6= 42
Move -6 to the other side.
8h-6+6= 42+6
8h= 48
divide by 8
8h/8= 48/8
h= 6
4(7x-8) + 6(5x+10)
Multiply the first bracket by 4
Multiply the second bracket by 6
28x-32+30x+60
= 58x+28
3(n+5)+2=26
Multiply the bracket by 3
3n+15+2= 26
3n+17= 26
3n+17-17= 26-17
3n= 9
divide by 3
3n/3= 9/3
n= 3